Efficacies of corynebacterium pseudotuberculosis vaccines against caseous lymphadenitis in mice and sheep - Osman Erganiş; H. Hüseyin Hadimli; Kürşat Kav; Aslı Sakmanoğlu; Zafer Sayın; Yasemin Pınarkara (Eurasian Journal of Veterinary Sciences)
Aim: This study was aimed to prepare Corynebacterium pseudotuberculosis vaccines against Caseous Lymphadenitis (CLA) and to determine the effectiveness of vaccines in mice and sheep.4 Materials and Methods: C. pseudotuberculosis vaccines were prepared in 3 different combination (PLD, bacterin and combined). Vaccines were subcutaneously administered twice (0.1 mL) 3 weeks intervals to mice. After vaccination at 15 days, mice were subcutaneously challenged with C. pseudotuberculosis and PLD of the challenge strain with LD50 dose. All mice were observed throughout 20 days for morbidity and mortality. Internal organs of deaths/euthanized mice were cultured for re-isolation of bacteria. Sheep were subcutaneously vaccinated twice (1 mL) with vaccines of commercial or combined, 3 weeks intervals. Blood sera were taken before and after vaccination at 45-60 days intervals. In addition, lymph nodes were examined microscopically by the presence any abscess. Antibody titers to C. psedotuberculosis in mice and sheep were determined by modified ELISA. Results: When compared to controls, antibody titers were significantly higher in vaccinated mice (P<0.05). In challenged trials with PLD, the ratio of morbidity and mortality was not observed in the vaccines groups PLD and combined. But, the lower ratio of morbidity and mortality in challenged trials with live bacteria were determined in the groups of bacterin and combined. When the levels of antibody in sheep were found to be high, abscess formation were lower in, comparison to controls. Conclusions: Especially combined C. pseudotuberculosis vaccines were concluded to be useful in prevention of CLA in sheep.